Efektivitas Penerapan Media Pembelajaran Video Dokumenter dalam Pembelajaran IPS pada Siswa SMP - Amirah Zahra Muthi; Nuraida Rezeki Fadhilah; Desy Safitri; Sujarwo Sujarwo (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The use of documentary video learning media can have a positive impact on the learning process, especially the understanding of complex concepts and their application in everyday life. Documentary videos can provide a deeper perspective and insight into real life, so it can be a window or tool to better see and understand real life. In this study, documentary videos have been evaluated in the context of Social Studies learning at the junior high school level. The literature review method was used to analyze various aspects of the use of documentary video learning media, including its impact on concept understanding and application in daily life. The results of this literature review provide an in-depth understanding of the factors that support the effectiveness of documentary video learning media, such as good design, content relevance, and instructional support. However, it also identifies some constraints, including the limited accessibility of technology and the need for teacher support in effective implementation. Thus, the findings from this study provide a strong basis for recommending the implementation of documentary video learning media in social studies learning in junior high schools. The practical implications can provide guidance for the development of more interesting and effective learning materials, by utilizing the potential of documentary videos as innovative and relevant learning aids.